The unmaking of Arab socialism - Ali Kadri (Anthem Press, 2016)
Conditions of malnutrition, conflict, or a combination of both characterize many Arab countries, but this was not always so. As in much of the developing world, the immediate post-independence period represented an age of hope and relative prosperity. But imperialism did not sleep while these countries developed, and it soon intervened to destroy these post-independence achievements. The two principal defeats and losses of territory to Israel in 1967 and 1973, as well as the others that followed, left in their wake more than the destruction of assets and the loss of human lives: the Arab World lost its ideology of resistance. The Unmaking of Arab Socialism is an attempt to understand the reasons for Arab world's developmental descent from the pinnacle of Arab socialism to its present desolate conditions through an examination of the post-colonial histories of Egypt, Syria, and Iraq.
Keywords: 330; Sozialismus; Wirtschaftsliberalismus; Wirtschaftslage; Arabische Staaten